The Triple $χ^{3}$ Sequence Spaces - Ayhan Esi; N. Subramanian (International Journal of Mathematics And its Applications, 2017)
Let $χ^{3}$ denote the space of all triple gai sequences and $Λ^{3}$ the space of all triple analytic sequences. This paper some theorems on general properties of $χ^{3}$ sequences have been established.